Pengaruh Price Discount, Shopping Lifestyle Dan Consumer Trust Terhadap Impulse Buying Pada Situs Marketplaces Shopee (Studi Pada Mahasiswa Feb Unisma Pengguna Aplikasi Shopee) - Yulia Dwi Tirtaasari; Nur Hidayati; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
Abstract The purpose of this study is to determine the effect Price Discount, Shopping Lifestyle, and Consumer Trust on Impulse Buying at Shopee, Faculty of Business Economics, Islamic University of Malang. This research uses an explanatory research type and a quantitative approach. The Malhotra theory was used to take samples, so a sample of 57 people was obtained. This research uses an explanatory research type and a quantitative approach. The Malhotra theory was used to take samples, so a sample of 57 people was obtained. To solve the problem in this cases using the validity test, reliability test, normality test, multiple linear regression test, multicollinearity test, heteroscedasticity test, classical assumption test. This study uses multiple linear regression analysis with the help of SPSS 26. The results of this study are that Price Discount, Shopping Lifestyle, and Consumer Trust variables affect Impulse Buying simultaneously, partially the Price Discount variable has no effect on Impulse Buying, while Shpping Lifestyle has no effect on Impulse Buying. Impulsive Buying, while Lifestyle Shpping has no effect on Impulsive Buying. and Consumer Trust partially influences Impulse Buying at Shopee, Faculty of Business Economics, Islamic University of Malang Keywords: Price Discount, Shopping Lifestyle, Consumer Trust, and Impulse Buying.